D2-SYNCHRONIZATION IN NONDETERMINISTIC AUTOMATA - Hanan Shabana (Ural Mathematical Journal)
We approach the problem of computing a D2-synchronizing word of minimum length for a given nondeterministic automaton via its encoding as an instance of SAT and invoking a SAT solver. In addition, we report some of the experimental results obtained when we had tested our method on randomly generated automata and certain benchmarks.